Is It Time to Redefine Cognitive Dysfunction after Cardiac Surgery? The Importance of Methodological Consistency - Sandro Glumac; Goran Kardum; Nenad Karanović (Acta Clinica Croatica, 2021)
High incidence and significance of repercussions on patient health and healthcare system make postoperative cognitive dysfunction (POCD) a major problem following cardiac surgery. POCD frequency drops over time since surgery and its occurrence are related to different aspects of cognitive deterioration that markedly impair the patient quality of life. Therefore, a substantial number of papers have focused on this complex postoperative complication, however, with limited achievement in clarifying it. The underlying mechanisms of POCD development and contributing factors are still unclear. A significant issue in POCD research is the lack of uniformity in defining cognitive impairment among investigators, including unique terminology of cognitive changes, a battery of appropriate neuropsychological tests, timing of assessment, and statistical approach. Thus, the aim of this review is to address the difficulties in establishing POCD definition, with inclusion of specific recommendations based on recent publications.